(untitled) (Ameghiniana, 2013)
In the first part of this paper, the author gives general information on the morphology, organization and story of the Corystospermaceous foliage. In the subsequent chapters, the author offers a key of genera and the revision of Dicroidium, Johnstonia and Xylopteris, with a total of 12 species. Under each taxon, the synonymy, types, features, remarks, geo and stratigraphical distribution are given. Photographs and drawings of each species are also given.